The State of Medicine Quality in the Mekong Sub-Region - Sauwakon Ratanawijitrasin; Souly Phanouvong (Institut de recherche sur l’Asie du Sud-Est contemporaine, 2021)
This study aims to increase awareness and interest on the pharmaceutical quality and counterfeit medicines issues in the Mekong Subregion. It provides a review of existing empirical findings regarding the state of medicine quality in the region. It also analyzes data on quality testing of drug samples from the five countries (Cambodia, China, Lao PDR, Thailand and Vietnam) in the region, in order to develop a conceptual framework for addressing the issue at the regional level, and to suggest areas for further study.